Evaluation of an off-feet heat response test for elite rugby sevens athletes - Fenemor, S. P.; Mills, B.; Sella, F. S.; Gill, N. D.; Driller, M. W.; Black, K.; Casadio, J. R.; Beaven, C. M. (Science & Sports, 2022)
A heat response test (HRT) assesses adaptations to heat stress and athlete readiness to perform in hot conditions. However, testing is often not sport-specific, and is challenging to incorporate into elite team-sports schedules due to competing training priorities. Seven non-heat acclimated elite rugby sevens athletes (25 ± 3 years; 95.3 ± 6.5 kg; 190 ± 3 cm) undertook two rugby sevens specific running tests in ambient (20 °C, 50% rH; RUN:AMB), and hot (35 °C, 80% rH; RUN:HOT) conditions, along with a heart rate (HR) matched cycling-based HRT (CYCLE:HOT). Physiological and perceptual variables were monitored throughout each test. Mean tympanic temperature (TTymp), HR, thermal sensation, rate of perceived exertion, and sweat loss significantly increased, while thermal discomfort and performance decreased in RUN:HOT compared with RUN:AMB, (all d > 1.40; p < 0.05). Significant reductions in mean TTymp and HR were evident in CYCLE:HOT compared with RUN:HOT (both d > 1.10; p < 0.05), whereas there were no clear differences in any perceptual variables. Mean peak TTymp was 39.5 ± 0.5 °C in RUN:HOT and 38.8 ± 0.4 °C CYCLE:HOT, respectively. Acute heat stress is detrimental to performance in non-heat acclimated elite rugby sevens athletes. High-intensity cycling in the heat can replicate the perceptual (but not the physiological) stress associated with high-intensity running in the heat. Cycling-based HRT could be used to avoid additional mechanical load associated with running-based heat testing.